PENGEMBANGAN DESAIN PINTU MASUK BUBU LIPAT BERDASARKAN ASPEK TINGKAH LAKU RAJUNGAN: Development of Collapsible Trap Entrance Design Based on Blue Swimming Crabs Behavior - Adi Susanto; Hery Sutrawan Nurdin; Ririn Irnawati; Mochammad Riyanto; Mohammad Ependi; Fahresa Nugraheni Supadminingsih; Asep Hamzah; Hendrawan Syafrie (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2021)
Blue swimming crab fishing using collapsible traps is widely used by fishermen because its caught live crabs and high selectivity. However, the passive fishing operation causes its low fishing productivity. The success of crabs fishing using folding traps is influenced by the suitability of the entrance design used. The size of the net and the inclination angle that are not by the crab's behavior will cause the crab to fail to be caught. This study aims to determine the more effective entrance design for catching crabs using the collapsible trap. The study was conducted in a laboratory using three mesh sizes, including 1.00, 1.25, and 1.50 inches with 30°, 40°, and 50° inclination angles. Each treatment combination uses different individual crabs. The study was conducted at night in an aquarium equipped with an infrared camera. Differences in mesh size and angle of inclination affect the crab's success rate and crawling speed in crossing the net field. The results showed that the highest percentage of crabs that successfully crossed the net field was obtained using a 1.25-inch mesh with an angle of 40°. The highest average crawling speed was also obtained at the same mesh size and angle of inclination. The use of a 1.25-inch mesh with an angle of 40° is expected to increase the effectiveness of catching crabs with folding traps.